Herdin health research and development information network. ([S.l] Herdin, 2006)
A computer program that searches the HERDIN database. It returns citations and/or abstracts of published Philippine health and medical literature from 1906-2006.
Version 2006.
"Published Philippine Health and Medical Literature from 1906-2006 (citations and abstracts)"-- from label.
Keywords: Medicine -- Philippines. -- Bibliography